Asuhan Keperawatan Jiwa Pada Tn.S DenganGangguan Isolasi Sosial Menarik Diri Di Rumah Sakit Jiwa Daerah Surakarta - Thoyib, Ibnu; , Wachidah Yuniartika, S.Kep., Ns (2015)
Intoduction : Human is social and therefore, isolating themselves makes comunnication and interaction failed. According to Riskesdas (2013) , people having psychological pressure are 1728 persons. National heavy psychological pressure is for 1,7%.In which there are 4021 clients of hospital treatment who suffer from halusination in RSJ Daerah Surakarta, 3980 client for violent behavior, 1754 clients for self unsufficiency, 1871 clients for low self-esteem and 401 clients for waham. Therefore, it is needed to educate people about how to make acquintance step by step in order to build good communication and interaction. Method : the weiter use descriptive method. The sample is Tn.S, the data were acquired by interview, observation, medical recording. Objektif : to know the nursing care of clients with by withdrawing include assessment, intervention, implementation, and evaluation of nursing. Results: after the nursery upbringing is achieved for 3x24 hours, the results show that clients can make a good relationship, know how to make acquintance gradually with other nurses and patients, make more friend of clients to tal to, increase the ability memorize. Summary:a diagnosis appearing on the clients isolation. In the application of social isolation to nursery upbringing on the Tn.S, the problem is solved. However for the family having nursery problems, the aim is not solved yet duetob the absent family. Keywords: social isolation, pulls away